Timing and frequency of oropharyngeal squamous cell carcinoma recurrences after treatment with curative intent - Autio Timo J; Atula Timo; Jouhi Lauri; Irjala Heikki; Halme Elina; Jouppila-Mättö Anna; Mäkitie Antti; Koivunen Petri (TAYLOR & FRANCIS LTD, 2025)
Background
The increasing number of patients under surveillance after treatment of human papillomavirus-related oropharyngeal squamous cell carcinoma (OPSCC) places a great burden on healthcare providers.
Aims/objectives
The aim of this study was to explore OPSCC recurrences in a long follow-up period: their site, frequency and timepoint after primary treatment, treatment and outcome. The secondary aim was to investigate if the recurrences are diagnosed on routine follow-up visits, and if the p16 status will have an effect on the pattern of recurrences.
Material and methods
We analyzed recurrences within a 10-year follow-up period after completed curatively intended treatment among OPSCC patients in Finland treated between 2000 and 2009. Patient-, tumor-, treatment- and follow-up -related parameters were investigated.
Results
Out of 495 patients with no residual tumor during the first six months, 71 (14%) were diagnosed with a recurrence, of which 47 were locoregional and 28 were treated with curative intent. Of the recurrences, 86% were diagnosed during the first 36 months after primary treatment. Only ten recurrences appeared after 36 months. The median OS after recurrence was 10.9 months.
Conclusions and significance
Routine follow-up longer than three years after treatment seems not to be effective in terms of detecting OPSCC recurrences.